FEM Modeling of Squeeze Film Damping Effect in RF-MEMS Switches - Syed Turab Haider; Muhammad Mubasher Saleem; Mashhood Ahmad (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
A very important aspect in the design of RF- MEMS switches, is to obtain low switching time. The switching time not only depends on the device geometric parameters but also on the operating conditions. This paper presents the squeeze film damping effect on the dynamic response of the RF-MEMS switches. The squeeze film damping effect, with and without perforations, on the switching time is analyzed using finite element method (FEM) simulations. The effect of temperature and humidity on the squeeze film damping and switching time is also investigated.